Rekrontruksi Mesin Frais Ajax Universal Model No. 2A Mark V Di Bengkel Mekanik Polman Negeri Bangka Belitung - Pristiansyah Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2018)
Mechanical workshop in Polman Bangka Belitung has 8 units Ajax Universal Milling Machine Model No. 2A Mark V. The condition of the engine can not be used maximum, for example a milling machine with a serial number FR12. This machine was damaged at the rotary speed control (rpm) and need repairing process. This study aims to analyze the types and causes damage to the rotary speed control, repair the damaged components and assemble the components to make it functioned with the standard engine. This research is devide in several stages, the first stage is analyzing the causes of the damage, the second stage is repairing and re-assembling the damage components. The last stage is testing for the repaired machine vibration by examining and comparing it with standard and permitted vibration machine and another machine which still good. The test results of the vibration machine is 0.884 mm / s rms for the axial direction and 0.938 mm / s rms for the radial direction. The summary, the vibration is still at the allowed limit which is equal to 1.12 mm / s rms and it means the machine is ready to use.